A Case study of Renato Choque - A Bolivian farmer using native potatoe diversity to manage degraded lands - Cadima, Ximena; Choque, Renato (2021)
The video provides an interesting story line of a farmer in Bolivia who is using native pottoe diversity to restore degraded lands. He is a custodian farmer conserving 5 varieties of native potatoes grown on degraded lands on his farm. He produces certified seed of these native potatoe varieties for distribution to to ther farmers. His farm is also used as a field school where he teaches farmers on production of quality seeds of native potatoes, control of pests and diseases and seed selection and preservation.